The Enforcement of Non-Discrimination Law and Sexual Minorities’ Rights in the EU: The Cases of Hungary and Poland - Jędrzejowska-Schiffauer, Izabela; Łączak, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The principle of equality and the prohibition of discrimination on grounds of sexual orientation are enshrined in the EU Treaties. A strong baseline is also laid down in secondary EU legislation. However, the impact of the respective provisions is constrained in two ways: by challenges to their enforcement and, regarding the secondary EU law, by limitations in their scope to employment. This paper takes stock of the EU non-discrimination law with respect to sexual minorities’ rights as well as the enforcement mechanisms applied by the EU to safeguard implementation in Member States. To contextualize the findings, we analyse the cases of Hungary and Poland where measures adopted by state and local authorities have led to decisive steps by the EU, including withholding financial transfers. The paper identifies systemic weaknesses in existing enforcement mechanisms and concludes by pointing to institutional reform which could address them.